Peningkatan Hasil Belajar Matematika Melalui Model Problem Based Learning Dengan Media Curipod Di Kelas XI SMK Negeri 2 Medan - Risna Ula Siregar; Saiful Bahri; Desniarti Desniarti; Seprianti Harahap; Rosalia Rusline Simanjuntak (Journal on Education, 2024)
The aim of this research is to improve students' mathematics learning outcomes through the problem-based learning (PBL) model using Curipod media. The research subjects consisted of 31 students of class XI TKR 4 at SMK Negeri 2 Medan, with data concentration measurement material. This type of research is classroom action research (PTK), which is carried out in two cycles, each cycle consisting of four stages: planning, implementation, observation and reflection. Based on the results of mathematics learning in the pre-cycle, it was found that only 8 out of 31 students or 25.8% achieved learning completeness, with a class average of 61.74. After implementing the PBL learning model using Curipod media in cycle I, the number of students who achieved learning mastery increased to 23 out of 31 students or 74.2%, with a class average of 76.68. At the end of cycle II, the number of students who achieved learning completion increased again to 28 out of 31 students or 90.3%, with a class average of 84.87. This shows an increase in student mathematics learning outcomes from pre-cycle to cycle II. Thus, it can be concluded that the application of the problem-based learning (PBL) model using Curipod media in class XI TKR 4 SMK Negeri 2 Medan can improve students' mathematics learning outcomes.